2021
DOI: 10.11604/pamj.2021.38.243.27132
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the tuberculosis control activities in Addis Ababa

Abstract: The first COVID-19 case was reported in Ethiopia on 13 th March 2020 and series of announcements of set of measures, proclamation and directives have been enacted to fight the coronavirus pandemic. These have implications for the regular health services including the TB control program. This brief communication assesses the impact of the COVID-19 response on the TB control activities of Addis Ababa health centers based on research project data. We compared the patient flows in pre-COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…Our observations are consistent with recent studies from Nigeria, Ethiopia, Malawi, Zimbabwe and elsewhere in SSA [14][15][16][17][18][19]. While these findings have been attributed largely to the direct effects of the COVID-19 lockdowns, Thakur et al and others [15][16][17] have suggested that other factors unrelated to the COVID-19 pandemic may be contributory.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our observations are consistent with recent studies from Nigeria, Ethiopia, Malawi, Zimbabwe and elsewhere in SSA [14][15][16][17][18][19]. While these findings have been attributed largely to the direct effects of the COVID-19 lockdowns, Thakur et al and others [15][16][17] have suggested that other factors unrelated to the COVID-19 pandemic may be contributory.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations are consistent with recent studies from Nigeria, Ethiopia, Malawi, Zimbabwe and elsewhere in SSA [14][15][16][17][18][19]. While these findings have been attributed largely to the direct effects of the COVID-19 lockdowns, Thakur et al and others [15][16][17] have suggested that other factors unrelated to the COVID-19 pandemic may be contributory. In Sierra Leone and other low-and middle-income countries (LMICs) in SSA, low health literacy rates; age-and gender-related differences in risk perception and care-seeking behavior; high out-of-pocket formal and informal costs of services; and transportation constraints are important barriers that commonly result in sub-optimal access and utilization of health services [20,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies conducted in different countries indicated a potential bidirectional link between TB and COVID-19. Patients with TB are more likely to experience poor outcomes from COVID-19 [25] and patients co-infected with COVID-19 and TB are more likely to suffer severe disease or death than patients with COVID-19 only [26]. The simultaneity of COVID-19 and pulmonary TB can issue a diagnostic dilemma [27] and new diagnostic challenges for clinicians [28].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, there have been limited studies conducted in the area, reporting that the series of COVID-19 containment measures that the government had taken, including state of emergency, had a significant impact on the overall TB care and treatment services in the country including a reduction in the flow of TB patients [38,39]. However, there has been no study that documented the impact of COVID-19 on patients with TB using real-time patient-level data.…”
Section: Introductionmentioning
confidence: 99%